Preparation and response surface optimization of lightweight porous structures - Kai HE; Xiangjun PEI; Xiaochao ZHANG; Qiang LI; QianRu HOU; Mengqi WANG; Shansong HUANG; Minghui MENG (Shuiwen dizhi gongcheng dizhi)
As a new type of building material structure, the porous structure still faces problems such as inaccurate optimal ratio and poor compatibility with plants, which affect its application. To determine the optimal ratio of porous structure and improve its mechanical strength while providing a good planting space, this study used lightweight porous volcanic stone as coarse aggregate, cement, fly ash, and water mixed into a cementitious slurry as a binder to produce lightweight porous materials. Relevant porous structure preparation experiments were conducted to explore its physical and mechanical properties at different single factor levels, and then a reasonable range of mix designs was obtained. Response surface methodology was used to obtain the optimal mix ratio of lightweight porous structure with certain compressive strength and good planting space and permeability. The results are as follows:(1)The compressive strength shows a trend of increasing first and then decreasing as the water cement ratio increases. The optimal water cement ratio is located around 0.35. The smaller the aggregate particle size, the higher the compressive strength of the porous structure. However, to meet the requirements of porosity and permeability, selecting an aggregate of about 2 cm is appropriate. (2)The cementitious material in the cementitious slurry is composed of 75% cement and 25% fly ash by mass and contains 0.1% water reducing agent. The dosage should be controlled between about 15%−25%, and should not exceed 30%. (3)Based on the response surface optimization analysis, the optimal mix design for preparing porous structures is as follows: The aggregate particle size is approximately 2 cm; the water cement ratio is 0.377, and the volume fraction of the cementitious slurry is 20.7%. At such design, the porosity, effective porosity, and permeability coefficient are 38.3%, 33.5%, and 2.98 cm/s, respectively. The porous structure under the optimal ratio not only meets its mechanical requirements, but also has good plant compatibility, which can provide the scientific basis for the preparation and application of porous structures.